PENERAPAN MODEL KOOPERATIF TIPE TEAM GAME TOURNAMENT UNTUK MENINGKATKAN AKTIVITAS SISWA DALAM PEMBELAJARAN ILMU PENGETAHUAN SOSIAL DI KELAS IV SEKOLAH DASAR NEGERI 08 PONTIANAK UTARA - ADHARI, AGUS (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe problem in this research is how to increase student activity in IPS learning using model of cooperative type TGT in class IV. The purpose of this research is to increase student activity in IPS learning using model co-operative type TGT in class IV. The method used is descriptive method with form of action research class, and is collaborative. The location of the research at SDN 08 Pontianak Utara, with the subject of research of teachers and students of class IV which amounted to 34 student. The technique used is direct observation technique, measurement, data collection tool using student activity indicator sheet, and data analysis used is calculate the average and percentage. This research is done as much as 3 cycles with the result of research is 1) student activity starting from cycle I 51,43%, cycle II 78,43%, and cycle III 89,82%. The average increase in student activity from cycle I to cycle II was 27%, the average increase of student activity from cycle II to cycle III was 11.39%, while the increase in student activity from cycle I to cycle III with an average of 38, 39%. From the data obtained can be concluded that by using cooperative model type TGT can increase student activity in class IV with very good category.Â Keywords: Enhancement, Student Activity, Model TGTÂ